Kemampuan Membaca Al-Qur’an Perspektif Metode Tilawati Studi Ilmu Pendidikan Islam - Izzan, Ahmad; Albarokah, Syahid (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
The Qur'an was revealed by Allah SWT as a testament to the truth of Prophet Muhammad SAW, with its primary function serving as guidance for humanity. The Qur'an addresses many aspects of education and its importance in human life. The ability to read the Qur'an is a proficiency or skill in correctly and accurately reciting the Qur'anic text or divine speech according to the rules of Tajweed. The Tilawati method is a learning approach for reading the Qur'an that employs tilawah melodies with a balanced approach, combining habituation through classical group practice and precision in reading through individualized techniques with the "listen and read" method. This study aims to address several research questions: 1) To describe the concept of the Tilawati method, 2) To elucidate the application of the Tilawati method in enhancing the ability to read the Qur'an, 3) To analyze the Qur'anic reading proficiency from the perspective of the Tilawati method within the framework of Islamic education. This research is classified as library research. The qualitative method is used to explore the sources. The data sources include primary sources, such as the Tilawati book and the strategies for teaching the Tilawati method, and secondary sources, including classical texts, books, journals, and other literature supporting this research. The findings indicate that the Tilawati method, by incorporating tilawah melodies, significantly enhances one's ability to read the Qur'an accurately and proficiently, in line with the principles of Tajweed. Consequently, the Tilawati method for Qur'anic reading involves a learning approach that uses the Rost melody, combining classical group and individualized methods. There are two pedagogical approaches in the Tilawati method that aid in Qur'anic reading proficiency: the classical approach and the individual approach. These findings contribute to the academic understanding of effective Qur'anic education techniques. Keywords : Qur'an, Tilawati Method, Proficiency, Reading